Discussion of Some Issues on the Calculation of the Gear Tooth Root Bending Stress in the Gear Bending Fatigue Test - Xu Kefei; Wang Dong; Liu Yufan; Zhang Erliang (Jixie chuandong)
Several issues of the calculation of the 18 Cr Ni Mo7- 6 carburized harden gear tooth root bending stress are discussed. The effects of the measuring direction of surface roughness Rzin the calculation of relative coefficient of tooth root surface condition YRrel Ton the accuracy of the results are analyzed. The effects of the deviation between the actual tensile strength and the reference tensile strength on the results of calculation are researched. Also,the static stress analysis is carried out on the tooth root bending stress by using the SolidWorks Simulation module,and the analytical results are close to the theoretical calculation results,which verifying the accuracy of the theoretical calculation results.